Bioaccessibility and bioactivity of Aloe vera juice fermented with probiotics: effect of in vitro gastrointestinal digestion - Cuvas-Limon, Ruth (2022)
Introduction Fruit and vegetable-based beverages, fermented with Lactic Acid Bacteria, are considered excellent functional foods with great bioactive properties like antioxidant and probiotic action [1]. This study aims to explore the antioxidant activity, and bioaccessibility of bioactive compounds from an Aloe vera juice fermented with probiotic LAB Enterococcus faecium and Lactococcus lactis. Methodology A. vera and the produced fermented juices were digested using the INFOGEST standardized in vitro gastrointestinal digestion protocol [2]. Total phenolic content and individual phenolic compounds (by UPLC) were determined during digestion. The radical scavenging activity (DPPH and ABTS) and Reducing Antioxidant Power (FRAP) was accessed in the A. vera and in both juices [3]. Results and conclusions A great release of phenolic compounds was observed during the intestinal phase, especially for the fermented A. vera juices. Since phenolics are mostly absorbed in the intestine, where they appear to be more bioaccessible, this shows an increased functionality of the produced fermented food. Fourteen phenolic compounds were identified in the juices, including hydroxybenzoic acids (vanillic, ellagic and 3,4-hydroxybenzoic acids), hydroxycinnamic acids (p-coumaric and ferulic acids), flavonols (kaempferol), flavan-3-ols (epicatechin and catechin), stilbene (resveratrol), flavanones (naringenin and hesperidin), flavone (quercetin and taxifolin) and anthracenes (aloin). Epicatechin, hesperidin and aloin were the compounds with highest concentration in juices. The fermentation of the A. vera increased the bioaccessibility of the A. vera biocompounds, particularly for kaempferol, ellagic acid, resveratrol, hesperidin, ferulic acid and aloin. Also, the A. vera phenolics released during digestion were able to reduce free radicals either by hydrogen donation, as assessed by ABTS test, or by electron donation, as assessed by the FRAP test. The efficacy of functional foods in providing therapeutic or physiological benefits depends largely on maintaining their bioavailability, and the antioxidants play a major role in the gastrointestinal tract by maintaining redox equilibrium against harmful oxidants, and preventing diseases linked to reactive oxygen species generated during digestion. Therefore, the developed probiotic A. vera juice will allow the use of natural resources for human health improvement, due to its potential as novel added-value functional beverage with great bioactive potential.